1920
DOI: 10.1002/andp.19203681705
|View full text |Cite
|
Sign up to set email alerts
|

Die Selbstdiffusionsgeschwindigkeit des geschmolzenen Bleis

Abstract: 86 4. Dts BeZb&d4~ebonageachwWd4gkedt dee ge8chrnoCrenen B W ; von J. O r 6 h urn& G . v. Heveey. 1)er Hrgriff der Selbstdiffutliori enttitammt J a m e s C: lark Maxwell.') Er ergibt sich unmittekar, sobald nian die lhffusion als Ergebnis der Molekularbewegung betrachtet; Nimmt man z. B. einen mit Stickstoff gleichmaSig gefiillten Zylinder und bezeichnet die in eineni Zeitpunkte an einem Ende des Zylinders befindlichen hlolekule rein fiktiv, d. h. ohne dabei ihrp Masse und Retlien xu beeinflussen, so kann man … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1921
1921
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…Von Hevesy first proposed and demonstrated the idea in 1920, [3][4][5] work for which he was later awarded a Nobel Prize. From the 1950s onward, with the spread of nuclear reactors and accelerators, a huge variety of suitable radioisotopes became available (suitable meaning that the half-life of the radioisotope is much longer than the time of the diffusion anneal), and it was then possible to study tracer diffusion in numerous material systems.…”
Section: Kinetics With Secondary Ion Mass Spectrometrymentioning
confidence: 99%
“…Von Hevesy first proposed and demonstrated the idea in 1920, [3][4][5] work for which he was later awarded a Nobel Prize. From the 1950s onward, with the spread of nuclear reactors and accelerators, a huge variety of suitable radioisotopes became available (suitable meaning that the half-life of the radioisotope is much longer than the time of the diffusion anneal), and it was then possible to study tracer diffusion in numerous material systems.…”
Section: Kinetics With Secondary Ion Mass Spectrometrymentioning
confidence: 99%
“…The sensitivity is increased by orders of magnitude and, when combined with ion implantation, it avoids the deposition of thin transition-metal layer on the amorphous material which leads to significant modifications of the recrystallization temperatures. Back in the twenties, the first solid state physics experiment using radioisotopes was reported by G. v. Hevesy with the study of self-diffusion in solid lead (1921) by using the natural radioactive isotopes 210 Pb and 212 Pb [29]. An older example of such a kind of studies at ISOLDE is the finding of anomalous diffusion of low concentrations of gold in amorphous silicon, where it is shown that interstitial diffusion of Au in a-Si is significantly retarded by the presence of intrinsic defects, presumably immobile vacancy-type defects which trap the Au atoms [30].…”
Section: Diffusion Studiesmentioning
confidence: 99%
“…The crystalline structure of solids has become a fundamental aspect in the modern understanding of solid-state diffusion mechanisms. Becquerel's discovery led to the pioneering work of Georg Hevesy, who first used radioactive isotopes as diffusion tracers [Groh, 1920]. Hevesy's work on the diffusion of radioactive lead isotopes in solid lead enabled the study of self-diffusion in solids [Groh, 1921;Hevesy, 1925].…”
Section: A Brief History Of Diffusionmentioning
confidence: 99%